2011
DOI: 10.1128/aac.05293-11
|View full text |Cite
|
Sign up to set email alerts
|

Sterilizing Activity of Novel TMC207- and PA-824-Containing Regimens in a Murine Model of Tuberculosis

Abstract: To truly transform the landscape of tuberculosis treatment, novel regimens containing at least 2 new drugs are needed to simplify the treatment of both drug-susceptible and drug-resistant forms of tuberculosis. As part of an ongoing effort to evaluate novel drug combinations for treatment-shortening potential in a murine model, we performed two long-term, relapse-based experiments. In the first experiment, TMC207 plus pyrazinamide, alone or in combination with any third drug, proved superior to the first-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
220
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(231 citation statements)
references
References 34 publications
(61 reference statements)
10
220
0
1
Order By: Relevance
“…On the other hand, continuing Z in the face of resistance may not provide any treatment-shortening benefit while increasing the risk of intolerance and/or toxicity, as observed with fluoroquinolone-Z combinations used to treat latent TB infection among MDR-TB contacts (46)(47)(48)(49). Given the favorable interactions between Z and new TB drugs in development and rising concerns over Z resistance among MDR-TB isolates, improved susceptibility testing methods for Z, including genotypic resistance testing, will continue to require attention in the future (50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, continuing Z in the face of resistance may not provide any treatment-shortening benefit while increasing the risk of intolerance and/or toxicity, as observed with fluoroquinolone-Z combinations used to treat latent TB infection among MDR-TB contacts (46)(47)(48)(49). Given the favorable interactions between Z and new TB drugs in development and rising concerns over Z resistance among MDR-TB isolates, improved susceptibility testing methods for Z, including genotypic resistance testing, will continue to require attention in the future (50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical testing, bedaquiline plus pyrazinamide had better sterilising activity than rifampicin, pyrazinamide, and isoniazid. 362 Bedaquiline displays notable synergy with pyrazinamide. 362 Spontaneous mutations conferring resistance to bedaquiline occur in approximately 1 in 10⁷ or 10⁸ bacteria (similar to rifampicin).…”
Section: Bedaquilinementioning
confidence: 99%
“…362 Bedaquiline displays notable synergy with pyrazinamide. 362 Spontaneous mutations conferring resistance to bedaquiline occur in approximately 1 in 10⁷ or 10⁸ bacteria (similar to rifampicin). 363 High-level resistance to bedaquiline results from mutations in the ATP synthase binding site, but such mutants have yet to be observed in clinical isolates.…”
Section: Bedaquilinementioning
confidence: 99%
“…The appropriate dilutions of the homogenates were plated on 7H11 agar enriched with 10% oleic acid-albumin-dextrose-catalase and rendered selective by supplementation with cycloheximide (10 mg/ml), carbenicillin (50 mg/ml), polymyxin B (25 mg/ml), and trimethoprim (20 mg/ml) to prevent contamination with minimal impact on M. tuberculosis growth (17). To detect and limit the consequences of clofazimine carryover, lung homogenates from the clofazimine-treated mice were plated in duplicate on 7H11 selective agar with and without 0.4% (weight/volume) activated charcoal, as Tasneen and colleagues have demonstrated that supplementation of the agar with this percentage of charcoal is effective in adsorbing clofazimine and minimizing carryover of the drug (18). For assessing relapse after treatment cessation in mice that received clofazimine, the lung homogenate was inoculated onto plain and charcoal-containing 7H11 agar plates.…”
Section: Mice and Aerosol Infectionmentioning
confidence: 99%